(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
Up the present, the Celtiberian funerary ritual by exposure to the vultures that Claudius Aelianus shows in De natura animalium, X, 22 has been accepted without any discusion in base to consider the reading vaccaei (absent in all the manuscripts), in order to explain the whole problem. In this article our aim is to hold a different hypothesis of research to clear the guiding lines of the critical panorama and to combine in adequate manner the historical and philological issues.